Socio-Economic Impact of Borobudur Temple Super Priority Tourism Development on The People of Borobudur Sub District - Sari, Mersa Ulia; Handoyo, Eko (Universitas Negeri Semarang, 2024)
The socioeconomic circumstances of a community can be positively impacted by the presence of tourism. The primary goal of advancing the tourism sector in the Borobudur Sub District area is now the growth of Super Priority Temple Tourism. More research is still necessary to fully comprehend the development's socioeconomic effects on the neighborhood. Analyzing the social and economic effects of the Borobudur Temple's high-priority tourism growth on the Borobudur Subdistrict community is the aim of this study. Qualitative research methodologies are used in this study. The Borobudur Sub District is the site of the study. The community, the secretary of the Borobudur Sub-District Head, and the tourism manager of the Borobudur Temple serve as the research's informants. Techniques for gathering data include documentation, interviews, and observation. The Modernization theory of Walt Whitman Rostow was the theory employed in this study. The study's findings demonstrate the favorable social effects of Borobudur Temple's top priority tourism growth, specifically higher levels of education and established collaboration. The economic impact on the community, on the other hand, is a rise in income as a result of more job openings, a wider range of employment options, and the emergence of new business ideas from the community. It is suggested that the expansion of Borobudur Temple as a top tourist destination necessitates coordination with other nearby tourist attractions, such as designing tour packages that simultaneously benefit all of the communities in the Borobudur Sub District. Additionally, the community should make the most of its current opportunities.